Promoting Face-to-Face Dialogue for Community Engagement in a Digital Age. Issue 4 (December 2017) - Scruby, Lynn S.; Canales, Mary K.; Ferguson, Evelyn; Gregory, David
Background: Health researchers in urban centers recognize the need to engage with inner-city community-based organizations. Funding for face-to-face engagement is often limited because most work done by agencies and academics now focuses on the use of digital technology. Purpose: This article presents reflections from a grant project aimed at establishing community engagement between academic health researchers and interdisciplinary inner-city community health and social service providers. Method: This study utilized a community-based participatory action approach. This study included a 1-day collaborative meeting to promote academic-agency engagement. During this meeting, the research participants brainstormed research priorities and used colored stickers to rank them. The research team met the following day to debrief the meeting and to begin analyzing the data together. Results: The findings from this project have stimulated dialogue among the agency partners and project team researchers with respect to current collaborations, services provided, and research priorities. Although digital or virtual meetings have their place, fostering community engagement through a face-to-face meeting proved invaluable to the participants. Conclusions: The success of this Canadian Institutes of Health Research-funded project demonstrates the value of academic-agency partnership, the positive aspects of gathering community, and engagement in better meeting the research needs of inner-city organizations.